VELOCIDADE DE CRESCIMENTO DE Trichoderma ISOLADOS DE Sclerotium rolfsii - COSTA, Brenda Fernandes; PESSÔA, Guilherme Martins; SANTOS, Stephany; BLANCO, Neder Henrique Martinez; GRAICHEN, Felipe André Sganzerla (ANAIS DO ENIC, 2023)
-